Principles and practices of management and organizational behaviour - Singh, Chandrani; Khatri, Aditi (London Routledge, 2024)
This book offers perspectives, insights, techniques, and approaches for efficient and contemporary management practices in an organization. It provides a comprehensive insight into the traditional and contemporary approaches of organizational behavior and their impact on organizational performance in the global era. Ranging from planning to staffing, and controlling to strategic decision-making, the case studies in the book incorporate relevant modern management models and correlate practices of management from organizational perspectives to allow any organization$1 (Bs direction and environment to be evaluated with suggested recommendations. This textbook consists of two broad parts. The first deals with management trends and functions ranging from the traditional era to the contemporary world. The second part explores the behavioral trends of organizations across domains to analyze the measures taken for improved productivity and sustainability.s
Keywords: Area Studies; Economics; Finance, Business & Industry